A multidisciplinary study of stigma among the Tausug in the Philippines - Paz, Consuelo J. 1933-; Medina, Isagani R.; Ventura, Elizabeth R. (1997)
Hansen's Disease or leprosy brings stigmatization from others and the sufferer himself. The process may be overt or covert with behavioral and psychological/emotional manifestations. A study among the Tausugs of Mindanao using a psycho-linguistic analysis of interviews, along with a psychological test and the use of archival data, among others, brings to light various perceptions, reactions and beliefs regarding causation as well as coping styles of hansenites, their kin and community members in an attempt to develop more culturally sensitive and appropriate educational materials for an HD control programme.